Mediation and mediatization in agrarian conflict in Indonesia on the Instagram accounts @wadas_ melawan and @rempang_melawan - Iskandar, Dudi; Sumardi, Eko; Azizah, Hesti Nur; Raharjo, Didik Hariyadi; Mukhlis, Khairani (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
The agrarian conflict in Indonesia was nothing new. In fact, it was rooted back to the Dutch colonial era hundreds of years ago. This meant that rural conflict in Indonesia had gone on for a very long time. However, the various solutions offered by stakeholders never satisfied all parties. There were always some who benefited, on the one hand, and others who were disadvantaged, on the other. Initially, rural conflict was limited to landowners, companies, and the state. In the era of social media, the conflict has lengthened. Instead of resolving the conflict, social media added to the long series of agrarian conflicts in Indonesia. When agrarian conflict was uploaded to social media, it became public consumption regardless of space and time. This research was a qualitative study that combined social media text analysis (Critical Discourse Analysis), particularly on Instagram, and field research. The initial focus of the research was on two Instagram accounts, @wadas melawan and @rempang melawan. The results of the study showed that social media, as a digital space, became an arena for conflicting parties to fight. As a virtual public space, social media was utilized by those in conflict over agricultural issues. Secondly, the best alternative for resolving agrarian conflicts was dialogic communication involving all interested parties. Lastly, the farm reform that the government had always echoed needed to be carried out by involving all interested parties.